The relationship between e-marketing mix framework (4Ps) and customer satisfaction with electronic information services: An empirical analysis of Jordanian university libraries - Efadel, Maha Waleed; Othman, Roslina; Nik Mat, Nik Hziman; Hamad, Faten Fatehi; Mohadis, Hazwani Mohd; Ahmed, Mahfooz (IOS Press, 2024)
This study employs Structural Equation Modeling (SEM) using Smart PLS 3.2.9 to offer valuable insight into the relationship between e-marketing mix (4Ps) and customer satisfaction with electronic information services provided by public university libraries in Jordan. The identified primary aspects within the e-marketing mix encompass e-product, e-pricing, e-place, and e-promotion. An online survey (questionnaire) targeting postgraduate student respondents at Jordanian public universities (a total of 792 participants) was used to gather data using a quantitative technique. Participants were chosen using voluntary response sampling. The study’s findings revealed that all relevant elements of the e-marketing mix establish significant relationships with customer satisfaction among postgraduate student respondents utilizing e-information services in public university libraries in Jordan. Notably, e-products, e-pricing, and e-promotion demonstrated substantial positive relationships with customer satisfaction. Conversely, there was a negative relationship observed with e-place. The novelty of this study lies in its exploration of the previously unexplored realm of the e-marketing mix framework (4Ps) in the context of customer satisfaction with electronic information services within university libraries in Jordan.